Contribution of Eastern Christianity to Development of Theology of Environment - Paul Haffner (Crkva u Svijetu, 2019)
Christian theology of creation contributes to the solution of ecological crisis, as a confirmation of the fundamental truth that the visible creature is a divine gift in itself, a “genuine gift” that creates “space” for personal communion. As a matter of fact, the correct Christian ecological theology is in the application of theology of creation. The term “ecology” combines two Greek words, oikos (house) and logos (word): physical environment of human existence can be seen as a kind of “habitat” for human life. Bearing in mind that the inner life of the Holy Trinity implies communion, the divine act of creation is absolutely free from the necessity of creating the participants who would take part in that communion. Therefore, it is possible to assert that the divine community has found its “habitat” in the created cosmos and it is possible to speak of the universe as a meeting place for the purpose of personal communion. This article provides insight into the contribution of Eastern Christianity to the theology of environment.